Mesenchymal Stem Cell-Derived Extracellular Vesicles in Tissue Regeneration. (21st March 2020) - Zhang, Bocheng; Tian, Xiaoyuan; Hao, Jun; Xu, Gang; Zhang, Weiguo
Mesenchymal stem cells (MSCs) are multipotent stem cells that have attracted increasing interest in the field of regenerative medicine. Previously, the differentiation ability of MSCs was believed to be primarily responsible for tissue repair. Recent studies have shown that paracrine mechanisms play an important role in this process. MSCs can secrete soluble molecules and extracellular vesicles (EVs), which mediate paracrine communication. EVs contain large amounts of proteins and nucleic acids, such as mRNAs and microRNAs (miRNAs), and can transfer the cargo between cells. The cargoes are similar to those in MSCs and are not susceptible to degradation due to the protection of the EV bimolecular membrane structure. MSC-EVs can mimic the biological characteristics of MSCs, such as differentiation, maturation, and self-renewal. Due to their broad biological functions and their ability to transfer molecules between cells, EVs have been intensively studied by an increasing number of researchers with a focus on therapeutic applications, especially those of EVs secreted by MSCs. In this review, we discuss MSC-derived EVs and their therapeutic potential in tissue regeneration.